Albumin‐binding of diclofenac and the effect of a site II inhibitor in the aqueous humor of cataract patients with the instillation of diclofenac. (12th February 2014) - Osaki, Takashi; Ozaki, Mineo; Takamura, Norito; Ogata, Kenji; Tokunaga, Jin; Setoguchi, Nao; Arimori, Kazuhiko
ABSTRACT Diclofenac instillation has been used widely in cataract surgery to prevent postoperative inflammation. Since diclofenac binds strongly to albumin in the circulation, it does not have a sufficient effect on patients in whom diclofenac binds strongly to albumin in the aqueous humor. A decrease in diclofenac binding and an increase in free diclofenac levels are necessary in these patients. The binding of diclofenac to albumin was investigated in the aqueous humor. In a diclofenac binding assay with albumin in the aqueous humor of individual patients, diclofenac was extracted from aliquots of the aqueous humor, and its total levels were measured using ultra high performance liquid chromatography (UHPLC). Free diclofenac levels were measured using ultrafiltration and UHPLC. The albumin‐binding fraction of diclofenac was 0.8 or higher in the aqueous humor of some patients. Ibuprofen significantly inhibited diclofenac binding to site II of albumin in mimic aqueous humor, but not in pooled aqueous humor. This difference may have been due to the weak binding of diclofenac to site II in the pooled aqueous humor. Flurbiprofen was used instead of diclofenac. Flurbiprofen has been shown to bind more strongly than diclofenac to the same site of albumin. Thus, the inhibitory effect of ibuprofen on the binding of flurbiprofen to albumin was investigated in pooled aqueous humor. The results indicated that ibuprofen significantly inhibited the flurbiprofen binding. An effective diclofenac administration method may be established for clinical application by the instillation of an appropriate inhibitor of binding to the albumin site II. Copyright © 2014 John Wiley & Sons, Ltd.